KONSEP BISNIS WISATA HALAL DALAM MENINGKATKAN PEREKONOMIAN DI INDONESIA - muhajir M. Nur Arsyad; Agus Ismawan; Khilda Amalia (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
This study's purpose is to explain the concept of halal tourism and its potential for future development. Because the concept of halal has now developed into the lifestyle of most of the population in Indonesia. The findings show that the tourism industry makes a major contribution to improving the welfare of a country or region as a whole. It is impossible to separate the actions and economic players engaged in tourism from the tourism industry as a whole since tourism is an economic activity.. These actors include community actors acting as customers, company actors acting as service providers, and the state as the regulator. According to the research results, the management of the halal sector must include halal components, both substances and methods of obtaining and processing them. A halal industrial area must have all these elements, including a halal management team, halal facilities and infrastructure, and halal allocation of all industrial plots. Islamic economic ideas and concepts guide the administration of the halal industry. In Islamic economics, all ideas and theories are sourced from the Qur'an and the Hadith of the Prophet.